Learning from preservice teachers' responses to trans-themed young adult literature: improving personal practice in teacher education. Issue 6 (1st November 2016) - Parsons, Linda T.
ABSTRACT: Tensions and contradictions in my personal practice and in the extant research prompted this study of preservice teachers' responses to trans-themed young adult literature. I adopted a self-study methodology to identify and address the shortcomings in my practice of including trans-themed literature in a Literature for Adolescents course. Through inductive analysis, I discovered that my students made statements related to literary, sociocultural, and personal themes. Next, I considered the data within and across themes to reflect on my personal practice. The students' responses suggest that I could improve my teaching practice by (1) guiding them to employ specific critical theories and analysis and (2) including multiple texts about the transgender experience. I propose and trouble these practices and consider the ways they confirm or contradict others' research regarding good teaching practices.